METHODOLOGY FOR DEVELOPING INFORMATION-ANALYTICAL COMPETENCE OF FUTURE FOREIGN LANGUAGE TEACHERS (TAMADDUN NURI JURNALI, 2024)
Although the right of every person to use, receive and dispose of information is guaranteed by law, it is prohibited by law to violate certain social order and security rules. That is why future foreign language teachers, who receive and exchange more information from more foreign sites and pages, can prevent these effects by developing the skills of analytical view of information and analytical analysis.